2010
DOI: 10.1007/s11420-010-9187-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Shrinkage for Shoulder Instability

Abstract: The online version of this article (doi:10.1007/s11420-010-9187-7) contains supplementary material, which is available to authorized users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 75 publications
0
29
0
Order By: Relevance
“…The use of radiofrequency‐induced thermal capsulorraphy has generated controversy in human literature. Failure rates of capsular shrinkage of 31% and 37% are described . Prosthetic reconstruction with suture anchors or bone tunnels is indicated in the most severe cases of MSI and in cases with poor response to conservative management.…”
Section: Introductionmentioning
confidence: 99%
“…The use of radiofrequency‐induced thermal capsulorraphy has generated controversy in human literature. Failure rates of capsular shrinkage of 31% and 37% are described . Prosthetic reconstruction with suture anchors or bone tunnels is indicated in the most severe cases of MSI and in cases with poor response to conservative management.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Toth et al 12 reported that leaving viable tissue between heat-treated regions, such as in a grid or stripe technique, improved the healing process after TCS. Researchers in 2 studies 15,18 specifically noted that minimal to no tissue was left during the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,[15][16][17][18][19][20] In addition to the different types and degrees of instability among the studies, surgical technique varied from a painting style that left no remaining tissue between the treated areas to a striping technique that left minimal tissue between passes. Postoperative management also varied in the period of immobilization and progression of exercises.…”
Section: Capsular-plication Studiesmentioning
confidence: 99%
See 2 more Smart Citations